1997
DOI: 10.1118/1.598108
|View full text |Cite
|
Sign up to set email alerts
|

A filtration method for improving film dosimetry in photon radiation therapy

Abstract: Successful radiotherapy requires accurate dosimetry for treatment verification. Existing dosimeters such as ion chambers, TLD, and diodes have drawbacks such as relatively long measurement time and poor spatial resolution. These disadvantages become serious problems for dynamic-wedged beams. Thus the clinical use of dynamic wedges requires an improved dosimetry method. X-ray film may serve this purpose. However, x-ray film is not clinically accepted as a dosimeter for photon beams, because it overresponds to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Furthermore, energy absorption coefficients for film emulsions and water differ significantly in the low energy region bellow 400 keV, as the data calculated according to Seltzer have shown 10. Since there is an enhanced contribution of scattered radiation to the total dose in modulated photon beams, a disadvantage of the film which shows over-response to low energy photons may become important 1113…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, energy absorption coefficients for film emulsions and water differ significantly in the low energy region bellow 400 keV, as the data calculated according to Seltzer have shown 10. Since there is an enhanced contribution of scattered radiation to the total dose in modulated photon beams, a disadvantage of the film which shows over-response to low energy photons may become important 1113…”
Section: Introductionmentioning
confidence: 99%
“…In addition, films have an increased sensitivity to x rays below 200 keV, so that the response varies with the field size and the depth in the phantom. 2,3 The response of the film also depends on the orientation of the film with respect to the incident radiation. 4 Finally, it was shown that the envelope material also has a slight influence on the dosimetric results obtained with films.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the low energy scatter to the film, 0.5-mm lead sheets were placed at 1.2 cm on both sides. (11) Film dosimetry was used only for relative measurements. An automatic film processor (FPM 2800, FUJI Photo Film Co., Tokyo, Japan) was used to develop the film.…”
Section: Methodsmentioning
confidence: 99%